Pengaruh Budaya Organisasi, Motivasi Kerja Dan Gaya Kepemimpinan Transformasional Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Di Mining Support Division PT Kaltim Prima Coal - Ardityas Gema Sasongko; Hairudinor Hairudinor; Muhammad Riduansyah Syafari (Universitas Lambung Mangkurat, 2021)
The Influence of Organizational Culture, Work Motivation and Transformational Leadership Styles on Employee Performance With Job Satisfaction as an Intervening Variable in the Mining Support Division of PT Kaltim Prima Coal.This study aims to test the influence of organizational culture (X1), work motivation (X2) and transformational leadership style (X3) on employee performance (Y2) through job satisfaction (Y1) in the Mining Support Division of PT Kaltim Prima Coal. This study took a sample of 62 respondent. While the data analysis techniques used are descriptive statistical analysis and path analysis.The results show the influence of organizational culture on positive but insignificant job satisfaction, the influence of transfomasional leadership motivation and style on positive and significant job satisfaction; the influence of organizational culture on employee performance is insignificant and positive; the influence of motivation and transformational leadership style on employee performance is significant and positive; and the effect of job satisfaction on employee performance is significant and positive.Keywords: Job Motivation, Work Discipline, Organizational Culture, Employee Performance